Lipophosphoglycan polymorphisms do not affect Leishmania amazonensis development in the permissive vectors Lutzomyia migonei and Lutzomyia longipalpis - Nogueira, Paula Monalisa (2017)
Fundação Oswaldo Cruz. Instituto René Rachou. Belo Horizonte, MG Brazil/Universidade Federal de Minas Gerais. Departamento de Parasitologia. Belo Horizonte, MG, Brazil